Feasibility Analysis of Groundwater Quality Impacted by Sugar Industry Activities in Kediri City Based on Physical, Chemical, and Biological Parameters: Analisa Kelayakan Kualitas Sumber Air Tanah Dampak Aktivitas Industri Gula di Kota Kediri Berdasarkan Parameter Fisika, Kimia, Biologi - Fidela Almadea; Restu Hikmah Ayu Murti; Muhammad Fajar (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Pesantren District is home to a large sugar factory. The presence of this sugar factory has environmental impacts, including its impact on the water environment. Groundwater is a major water source for hygiene and sanitation activities in Pesantren District. Groundwater resources are vulnerable during the transitional seasons. Rivers flowing from the factory, carrying materials, overflow and seep into the ground. Groundwater quality testing in Pesantren District was conducted by taking samples to a laboratory to determine the suitability of the water for hygiene and sanitation activities within the surrounding community. The test results examined physical, chemical, and biological parameters, in accordance with Minister of Health Regulation No. 2 of 2023. Several sampling points were found to contain parameters exceeding quality standards. The results of this activity recommend improving the quality of wastewater from the sugar factory and conducting regular water quality testing to ensure its suitability for public use.